2002
DOI: 10.1088/0022-3727/35/23/311
|View full text |Cite
|
Sign up to set email alerts
|

Glass filler charged epoxy resin experimental validation of boundary integral equation method for computing effective permittivity of two and three phase composites

Abstract: The effective characteristics of composite materials depend on their inner structure. In this paper, we carry experimental validation of the computer simulations based on boundary integral equation method used for investigating the effective permittivity of two- and three-phase heterogeneous materials with cylindrical, spherical and hollow-spherical glass inclusions embedded in epoxy resin matrix. The results are also compared with the analytical formulae predictions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…This outlines the lower values for the numerical model in comparison to the analytical one [21]. Further interests should be especially paid to the type of fillers, their geometrical shapes and their volume fraction within the polymer matrix for their contribution in polarization phenomena [79].…”
Section: Charging Of Electric Particlesmentioning
confidence: 95%
“…This outlines the lower values for the numerical model in comparison to the analytical one [21]. Further interests should be especially paid to the type of fillers, their geometrical shapes and their volume fraction within the polymer matrix for their contribution in polarization phenomena [79].…”
Section: Charging Of Electric Particlesmentioning
confidence: 95%
“…3 Even the simple blending of silica microparticles with organic polymers often improves the competences of the materials. 4 The sol-gel method is effective for blending inorganic components at the nano level. 2, 3 Since alkoxysilanes and organic compounds (monomers or polymers) can form homogeneous solutions in some cases, these mixed systems are advantageous to nanocomposite syntheses.…”
Section: Introductionmentioning
confidence: 99%
“…It is well claimed that a filler silica mixed with a cured epoxy resin enhances the thermal stability of the corresponding material. 4,9 Therefore, nanocomposite materials of epoxy resin and silica are expected to have improved thermal and chemical resistances and mechanical properties. It was reported that molecular level mixing of epoxy resin and silica can be performed by the concurrent reactions of pre-polymers of epoxy resins with alkoxysilanes.…”
Section: Introductionmentioning
confidence: 99%
“…The virtues of the BIEM put it in a very important position among numerical methods, and in our previous analysis of heterogeneous structures the BIEM was found to be advantageous compared with predictions using analytical formulae concerning heterogeneous media. We carried out experimental verification of the BIEM [8], which showed that it permits us to calculate precisely the effective permittivity of composite materials with regularly shaped inclusions periodically distributed in the host matrix. We also applied the BIEM to the inverse problem, where we predicted globally the grain shape of irregular inclusions based on measurements of the effective characteristics of the composite [9].…”
Section: Introductionmentioning
confidence: 99%